Exercise prehabilitation during neoadjuvant chemotherapy may enhance tumour regression in oesophageal cancer: results from a prospective non-randomised trial. Issue 7 (1st February 2022) - Zylstra, Janine; Whyte, Greg P; Beckmann, Kerri; Pate, James; Santaolalla, Aida; Gervais-Andre, Louise; Russell, Beth; Maisey, Nick; Waters, Justin; Tham, Gemma; Lagergren, Jesper; Green, Michael; et al.
Abstract : Background: There is increasing evidence for the use of exercise in cancer patients and data supporting enhanced tumour volume reduction following chemotherapy in animal models. To date, there is no reported histopathological evidence of a similar oncological benefit in oesophageal cancer. Methods: A prospective non-randomised trial compared a structured prehabilitation exercise intervention during neoadjuvant chemotherapy and surgery versus conventional best-practice for oesophageal cancer patients. Biochemical and body composition analyses were performed at multiple time points. Outcome measures included radiological and pathological markers of disease regression. Logistic regression calculated ORs with 95% CI for the likelihood of pathological response adjusting for chemotherapy regimen and chemotherapy delivery. Results: Comparison of the Intervention (n=21) and Control (n=19) groups indicated the Intervention group had higher rates of tumour regression (Mandard TRG 1–3 Intervention n=15/20 (75%) vs Control n=7/19 (36.8%) p=0.025) including adjusted analyses (OR 6.57; 95% CI 1.52 to 28.30). Combined tumour and node downstaging (Intervention n=9 (42.9%) vs Control n=3 (15.8%) p=0.089) and Fat Free Mass index were also improved (Intervention 17.8 vs 18.7 kg/m 2 ; Control 16.3 vs 14.7 kg/m 2, p=0.026). Differences in markers of immunity (CD-3 and CD-8) and inflammation (IL-6, VEGF, INF-y, TNFa, MCP-1 and EGF) were observed. Conclusion: The results suggest improved tumour regression and downstaging in the exercise intervention group and should prompt larger studies on this topic. Trial registration number: NCT03626610 .